An Annotated Bibliography of Recent Research on Labour Relations Policy, Unionization, and Canada-U.S. Labour Market Performance - Sran, Garry (Just Labour: A Canadian Journal of Work and Society, 2009)
[This] is an annotated list of selected recent publications on unionization and labour market performance, with relevance to Canada-U.S. labour market comparisons and the effect of collective bargaining structures on economic and social outcomes. While the broad literature on this topic is vast, the publications summarized below seem to be germane to Canadian aspects of the U.S. Employee Free Choice Act debate that are considered in this special issue of Just Labour. –Introduction